2011
DOI: 10.1021/jp109788r
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Formation in Polyelectrolyte−Micelle Complex Coacervation

Abstract: The temperature-induced liquid-liquid phase transition (complex coacervation) of a polycation-anionic/nonionic mixed micelle system was examined over a range of macroion concentrations and polycation molecular weights (MW) using turbidimetry and dynamic light scattering (DLS). DLS revealed a progressive increase in complex/aggregate size with temperature up to the phase transition at T(φ), followed by splitting of these clusters into respectively smaller and larger particles. We present two explanations: (1) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 61 publications
1
40
0
Order By: Relevance
“…The CAC of neutral polymer-surfactant complexes decreases with increasing temperature [40,42] due to a decrease in hydrophilicity with increased temperature, as demonstrated for polyethylene oxide (PEO) with the cationic surfactant hexadecyltrimethylammonium chloride (HTAC). For highly-charged polyelectrolyte systems, there is an influence of temperature, however the system is more strongly influenced by the electrostatic interactions, which have only a minor temperature dependence [3,37,43,44,45].…”
Section: Intermolecular Interactionsmentioning
confidence: 99%
“…The CAC of neutral polymer-surfactant complexes decreases with increasing temperature [40,42] due to a decrease in hydrophilicity with increased temperature, as demonstrated for polyethylene oxide (PEO) with the cationic surfactant hexadecyltrimethylammonium chloride (HTAC). For highly-charged polyelectrolyte systems, there is an influence of temperature, however the system is more strongly influenced by the electrostatic interactions, which have only a minor temperature dependence [3,37,43,44,45].…”
Section: Intermolecular Interactionsmentioning
confidence: 99%
“…However, as the mechanism of cluster formation via a balance between long-range repulsion and short-range attraction, although not widely appreciated, is now firmly established, it is timely to revisit the problem of complex coacervation from this perspective. Indeed, the behaviour of polyion-surfactant mixtures has already been discussed in this light 70 , but here we focus exclusively on oppositely-charged polyion mixtures that form complex coacervates.…”
Section: Complex Coacervatesmentioning
confidence: 99%
“…Moreover, Kizilay et. al 70 emphasize the propensity of complex coacervates to form from small near-neutral complexes of oppositely-charged polyions. This provides a clue as to how complex coacervates might be modelled in terms of the SALR model.…”
Section: Complex Coacervatesmentioning
confidence: 99%
“…Weiß et al 78 observed a temperature dependency for the system of hydroxypropyl methylcellulose phthalate, where formed coacervates precipitated at a critical temperature. Kizilay et al 79 explained that at a critical temperature the formed clusters first grow in size, followed by separation into larger and smaller colloidal clusters due to macroion disproportionation. Dubin et al 80 also observed this critical temperature for both dilute and concentrated polyelectrolyte mixtures.…”
Section: Extrinsic Factorsmentioning
confidence: 99%